2011
DOI: 10.1007/s00018-011-0855-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards in vitro molecular diagnostics using nanostructures

Abstract: Nanostructures appear to be promising for a number of applications in molecular diagnostics, mainly due to the increased surface-to-volume ratio they can offer, the very low limit of detection achievable, and the possibility to fabricate point-of-care diagnostic devices. In this paper, we review examples of the use of nanostructures as diagnostic tools that bring in marked improvements over prevalent classical assays. The focus is laid on the various sensing paradigms that possess the potential or have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“… 16 25 On the basis of current trends in the development of nanoISFET-based sensor platforms and bioassays, it is suggested that label-free detection approaches may soon provide breakthroughs in the field of in vitro diagnostics (IVD) and compete against otherwise tedious and expensive bioanalytical methods involving preamplification of analytes, for example, polymerase chain reactions (PCRs) and enzyme-linked immunosorbent assays (ELISAs). 3 , 26 30 …”
Section: Introductionmentioning
confidence: 99%
“… 16 25 On the basis of current trends in the development of nanoISFET-based sensor platforms and bioassays, it is suggested that label-free detection approaches may soon provide breakthroughs in the field of in vitro diagnostics (IVD) and compete against otherwise tedious and expensive bioanalytical methods involving preamplification of analytes, for example, polymerase chain reactions (PCRs) and enzyme-linked immunosorbent assays (ELISAs). 3 , 26 30 …”
Section: Introductionmentioning
confidence: 99%
“…Detection of biomolecules is fundamentally important in a number of fields such as environmental analysis, identification of biological threats and in medical diagnosis. Among all these application areas, modern molecular diagnostics has been the driving force for the extensive research on nanoscale biosensors . The current trend in the domain of medical sciences is to investigate the molecular basis of various diseases rather than attempt just a symptomatic treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Since the synthesis of the first carbon nanostructures, such as fullerene C 60 (0D) [27] and CNTs (1D) [28] (Figure 2), there has been a tremendous effort for understanding the properties of these nanomaterials and for exploring the broad range of applications in which they can be used. Carbon-based nanomaterials (CNMs) have created a great deal of interest in various applications such as optical imaging [29], drug and gene delivery [30], and nanotherapeutics [31,32] due to their excellent mechanical, optical and electrical Review of In Vitro Toxicity of Nanoparticles and Nanorods-Part 2 http://dx.doi.org/10.5772/intechopen.78616…”
Section: Carbon Nanostructuresmentioning
confidence: 99%